Research progress and application of CO2 flooding oil storage: A review - HE Qi; SONG Weibin; HAN Ying (矿业科学学报)
The CO2 flooding and sequestration technology displays significant effect in CO2 emission reduction and oil displacement, which could alleviate global warming, achieve China's dual carbon goals and sustainable development. This study reviews existing CO2-EOR projects with 100 000 tons and above, with a focus on domestic engineering cases. Specifically, we analyzed such major issues as technology matching, safety monitoring, economic constraints and legal policy preference in implementing CO2-EOR projects in China, and discussed its future prospects. The implementation of this technology shows a late start in China and still lags behind those in Europe and the USA due to a lack of large-scale commercialized projects. By drawing on foreign scholarly efforts, we need to optimize the whole process of CO2 flooding and storage through the introduction of artificial intelligence, upgrade CO2 leakage risk identification and control as well as CO2 dynamic monitoring to accelerate the commercialization and industrialization of large-scale CO2-EOR projects.